Street of shame. (Economist, 2011)
The article focuses on the revelation that the tabloid "News of the World" routinely and illegally hacked into the mobile-phone mailboxes of British celebrities, citizens, and politicians, and what should be done about it. It states Britain's newspaper market is extremely competitive and suggests the silence of other newspapers over the hacking of phone mailboxes hints that other papers are also guilty. It calls for a full judicial inquiry with power to call witnesses under oath to be launched.